2021
DOI: 10.1136/bmjgh-2020-004406
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric surgical outcomes in sub-Saharan Africa: a multicentre, international, prospective cohort study

Abstract: IntroductionAs childhood mortality from infectious diseases falls across sub-Saharan Africa (SSA), the burden of disease attributed to surgical conditions is increasing. However, limited data exist on paediatric surgical outcomes in SSA. We compared the outcomes of five common paediatric surgical conditions in SSA with published benchmark data from high-income countries (HICs).MethodsA multicentre, international, prospective cohort study was undertaken in hospitals providing paediatric surgical care across SSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…A recent prospective cohort study spanning 19 Sub-Saharan African (SSA) countries demonstrated that mortality from pediatric surgical disease is signi cantly higher in SSA than HIC: gastroschisis (75.5% vs 2.0%), anorectal malformation (11.2% vs 2.9%), intussusception (9.4% vs 0.2%), appendicitis (0.4% vs 0.0%) and inguinal hernia (0.2% vs 0.0%), respectively. [19] Our ndings suggest that delay in surgical treatment is likely a contributing factor and that COVID-19 exacerbated these delays.…”
Section: Discussionmentioning
confidence: 77%
“…A recent prospective cohort study spanning 19 Sub-Saharan African (SSA) countries demonstrated that mortality from pediatric surgical disease is signi cantly higher in SSA than HIC: gastroschisis (75.5% vs 2.0%), anorectal malformation (11.2% vs 2.9%), intussusception (9.4% vs 0.2%), appendicitis (0.4% vs 0.0%) and inguinal hernia (0.2% vs 0.0%), respectively. [19] Our ndings suggest that delay in surgical treatment is likely a contributing factor and that COVID-19 exacerbated these delays.…”
Section: Discussionmentioning
confidence: 77%
“…The appendix location is a crucial information which guide the ~ 8 ~ surgical incision as almost all appendectomies are done in with the open fashion in our environment [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Acute appendicitis (AA) is the most common digestive emergency in pediatric surgery [1,2] . In LMICs, it is still a challenging disease which still has a higher morbidity and mortality [3] . Acute appendicitis usually depicts a classical clinical presentation.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] There are multiple reasons for these poor outcomes including inadequate training in pediatric anesthesia, lack of pediatric specific standardized care pathways and inadequate pediatric specific equipment and physiologic monitoring capabilities. 23,25,26 Broad prospective perioperative data collection is needed to better understand the problems including the burden of pediatric surgical complications. Risk factors and types of complications need to be identified to enable the development of appro-…”
Section: The Data Challeng Ementioning
confidence: 99%